PENGARUH PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR ELEKTRONIKA KELAS X TKR SMKN 1 PALANGKA RAYA - Irvan Wahyu Dinata; Debora; Jhonni Rentas Duling (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2019)
The purpose of this study was to determine the effect of scramble learning model on automotive basic technology of electronics lesson on learning outcomes of class X TKR student of SMKN 1 Palangka Raya. This type of research uses true experiment design, the form of research design used in this study uses the form of the pretest and posttest control group design type wherein the initial test will be given before treatment is given and the final test will be given before treatment. The results of this study indicate that the calculation using the t test with a significance level of ? = 0.05 obtained a value of 6.24 while the value of 2.005. This means that H0 is rejected and H1 is accepted, so it can be concluded that there is an influence of student learning outcomes taught using the Scramble learning model on the basics of electronics lesson